Selective Neural Deletion of the Atg7 Gene Reduces Irradiation-Induced Cerebellar White Matter Injury in the Juvenile Mouse Brain by Ameliorating Oligodendrocyte Progenitor Cell Loss - Wang, Yafeng; Zhou, Kai; Li, Tao; Xu, Yiran; Xie, Cuicui; Sun, Yanyan; Rodriguez, Juan; Zhang, Shan; Song, Juan; Wang, Xiaoyang; Blomgren, Klas; Zhu, Changlian (Frontiers in Cellular Neuroscience, 2019)
Radiotherapy is an effective tool for treating brain tumors, but irradiation-induced toxicity to the normal brain tissue remains a major problem. Here, we investigated if selective neural autophagy related gene 7 (Atg7) deletion has a persistent effect on irradiation-induced juvenile mouse brain injury. Ten-day-old Atg7 knockout under a nestin promoter (KO) mice and wild-type (WT) littermates were subjected to a single dose of 6 Gy whole-brain irradiation. Cerebellar volume, cell proliferation, microglia activation, inflammation, and myelination were evaluated in the cerebellum at 5 days after irradiation. We found that neural Atg7 deficiency partially prevented myelin disruption compared to the WT mice after irradiation, as indicated by myelin basic protein staining. Irradiation induced oligodendrocyte progenitor cell (OPC) loss in the white matter of the cerebellum, and Atg7 deficiency partly prevented this. The mRNA expression of oligodendrocyte and myelination-related genes (Olig2, Cldn11, CNP, and MBP) was higher in the cerebellum in Atg7 KO mice compared with WT littermates. The total cerebellar volume was significantly reduced after irradiation in both Atg7 KO and WT mice. Atg7-deficient cerebellums were in a regenerative state before irradiation, as judged by the increased OPC-related and neurogenesis-related transcripts and the increased numbers of microglia; however, except for the OPC parameters these were the same in both genotypes after irradiation. Finally, there was no significant change in the number of astrocytes in the cerebellum after irradiation. These results suggest that selective neural Atg7 deficiency reduces irradiation-induced cerebellar white matter injury in the juvenile mouse brain, secondary to prevention of OPC loss.